Exploration of student learning obstacles in solving propotional problems in junior high school - Warli, Dwi; Fatimah, Siti; Wicaksono, Agung; Kahar, Moh Jusri; Fajriani, Fajriani; Deeteng, Asman (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Background: Proportion is a key mathematical concept, but epistemological and didactical learning obstacles can hinder students' understanding. These challenges arise from limited contextual knowledge and procedural teaching methods. Identifying these obstacles through diagnostic assessments helps design effective learning strategies, enhancing students' proportional reasoning and problem-solving skills. Aim: This research aims to describe and analyze students' learning obstacles in Proportion material in terms of Proportional reasoning.. Method: The method used in this case is a research method qualitative focuses on obstacles to learning. Instruments used in studying learning obstacles designed based on the Proportional level of reasoning. The subject of this research comes from Al-Fahmi Palu Junior High School which consists of class VII, Data collection was carried out through written tests, interviews and observations. Result: The results of the research show revealing two main types: epistemological and didactical obstacles. Epistemological obstacles arise due to students' limited contextual knowledge, preventing them from applying known concepts to new problems, as seen in their difficulty modeling proportional relationships correctly. Didactical obstacles stem from procedural teaching methods that emphasize memorization over conceptual understanding, leading students to rely on fixed procedures rather than flexible problem-solving strategies. These findings highlight the need for varied and meaningful learning approaches to help students build a deeper understanding of Proportion concepts. Conclusion: The research found two types of student learning obstacles in solving Proportion problems: epistemological obstacles, due to limited contextual knowledge, and didactical obstacles, arising from teachers' procedural teaching methods and lack of varied practice, leading to difficulties in handling complex proportional reasoning.